Լոռե բերդաքաղաքի 2022-2023 թթ. պեղումների հիմնական արդյունքները - Նալբանդյան, Արման (ՀՀ ԳԱԱ Պատմության ինստիտուտ)
The Lore fortified town, located in the Lori fortress community in Lori region, is one of the best preserved fortresses in Armenia. This remarkable fortress of Gugark land, was created on the promontory formed at the confluence of the Dzoraget and Urut rivers, which is surrounded by steep cliffs. It is located at an altitude of 1490 m above the sea level, and together with the suburbs, occupied an area of 50-60 ha (the citadel alone – 9 ha). With a separate grant from the Ministry of Education, Science, Culture and Sport of the Republic of Armenia, within the framework of the restoration and improvement program, the expedition of the “Scientific Research Center for Historical and Cultural Heritage” (director – Kh. Harutyunyan) resumed the excavations of Loreberd fortified town in May, 2022 (expedition leader: A. Nalbandyan). Excavations were carried out in the following areas; a) The previously unexcavated area adjacent to the inside of the fortress wall, b) layers visible on the fortress wall, c) small (second) bathroom, d) inside and around the large (the first) bathroom.
Keywords: Մշակույթ; Պատմություն